2004
DOI: 10.1111/j.1365-2958.2004.04282.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo inducible gene of Pseudomonas aeruginosa encodes an anti‐ExsA to suppress the type III secretion system

Abstract: SummaryWe have previously reported on the isolation of in vivo inducible genes of Pseudomonas aeruginosa using IVET system. One of such genes isolated from burn mouse infection model encodes a short open reading frame with unknown function. In this study, we demonstrate that this gene product specifically suppresses the expression of type III secretion genes in P. aeruginosa , thus named PtrA (Pseudomonas type III repressor A). A direct interaction between the PtrA and type III transcriptional activator ExsA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 55 publications
0
74
1
Order By: Relevance
“…This process represents the positive activation loop of the T3SS that is triggered by cell contact in vivo and can be mimicked by calcium depletion in vitro. Besides this major regulatory operon, other factors regulate T3SS expression, including cyclic AMP with Vfr, the Pseudomonas catabolite repression homologue (Wolfgang et al, 2003), PtrA (Ha et al, 2004) and the RetS/LadS/GacAS two-component regulatory systems (Goodman et al, 2004;Laskowski et al, 2004;Ventre et al, 2006;Zolfaghar et al, 2005). Taken together, these published data indicate that P. aeruginosa uses a complex set of signalling pathways both to activate and to repress T3SS expression in response to extracellular and intracellular triggers (Yahr & Wolfgang, 2006).…”
Section: Introductionmentioning
confidence: 59%
“…This process represents the positive activation loop of the T3SS that is triggered by cell contact in vivo and can be mimicked by calcium depletion in vitro. Besides this major regulatory operon, other factors regulate T3SS expression, including cyclic AMP with Vfr, the Pseudomonas catabolite repression homologue (Wolfgang et al, 2003), PtrA (Ha et al, 2004) and the RetS/LadS/GacAS two-component regulatory systems (Goodman et al, 2004;Laskowski et al, 2004;Ventre et al, 2006;Zolfaghar et al, 2005). Taken together, these published data indicate that P. aeruginosa uses a complex set of signalling pathways both to activate and to repress T3SS expression in response to extracellular and intracellular triggers (Yahr & Wolfgang, 2006).…”
Section: Introductionmentioning
confidence: 59%
“…Expression of this gene is specifically inducible by high copper signal in vitro through a CopR/S two-component regulatory system, suggesting an important in vivo signal during infection of burn mouse skin tissue (17,36). Also, we have shown that mutation in a mucA gene not only activates alginate production but also represses the expression of the TTSS (50).…”
mentioning
confidence: 82%
“…Recently, we have demonstrated that a gene highly inducible during infection of the burn mouse model, designated ptrA, encodes a small protein which inhibits TTSS through direct binding to ExsA and thus functions as an anti-ExsA factor (17). Expression of this gene is specifically inducible by high copper signal in vitro through a CopR/S two-component regulatory system, suggesting an important in vivo signal during infection of burn mouse skin tissue (17,36).…”
mentioning
confidence: 99%
“…cop boxes are found in promoters preceding P. syringae copA (24) and E. coli cusC (10) and pcoA (26). For P. aeruginosa, PA2808 (ptrA), which precedes cinA, has been reported to be induced by copper (14, 36) via a mechanism involving the two-component system cinRS (PA2809 and PA2810) and resulting in the repression of the type III secretion system (14).…”
Section: Discussionmentioning
confidence: 99%